HEARING LOSS AS AN INDICATOR OF CAROTID ARTERY STENOSIS: MECHANISMS, DIAGNOSIS, AND TREATMENT - Khaydarova G.S; Shodmonkulova G.R (TADQIQOTLAR, 2025)
Carotid artery stenosis (CAS) is an underrecognized contributor to sensorineural hearing loss (SNHL). The underlying vascular mechanisms and implications for stroke risk require further exploration. Objective:To summarize the prevalence, pathophysiology, diagnostic tools, and treatment options for CAS-related SNHL. Methods:A review of current literature, including epidemiological data, vascular pathophysiology, imaging modalities, biomarkers, and emerging therapies. Results:Approximately 10–30% of CAS patients experience SNHL before major cerebrovascular events. Inflammatory pathways, oxidative stress, and endothelial dysfunction contribute to cochlear ischemia. Advanced imaging techniques, such as functional MRI and transcranial Doppler ultrasound, offer early detection of vascular-induced hearing loss. Pharmacologic interventions (vasodilators, antioxidants, statins) and cochlear implants may improve outcomes. Conclusion:Hearing loss may serve as an early biomarker for carotid disease. Routine audiometric screenings in high-risk populations could aid early intervention and stroke prevention. Further studies are needed to assess the impact of vascular interventions on hearing function.